Drawing guessing game for the elderly - Foo, Wai Yip *; Lim, Woan Ning *; Lee, Chien Sing * (2017)
Drawing guessing game is the game where the users are required to guess the item that is progressively drawn on the screen. In this project, an elderly oriented mobile drawing guessing game named Guess It was developed. This application allows the drawings to be added into the cloud database from time to time and get downloaded to the user’s mobile devices without the need to update the application. The time taken to complete each game can be recorded to monitor the progress of the elderlies who plays the game. The aim of this project is to develop an elderly friendly mobile game by incorporating the elderly gaming design guidelines and by considering the elderly’s limitations, to foster the interest of the elderly in mobile gaming. Survey was carried out with a group of elderlies at the end of the project to gauge their confidence and satisfaction level in the developed game.